The Influence of Demonstration Learning Method on Students’ Learning Motivation and Working Skills at Permahisa Vocational School on Hospitality And Tourism Services Major - Fajriyah, Nurul; Kusmiyati, Kusmiyati; Purnamasari, Hetty (UNDIKMA, 2024)
This research aims to find out the influence of demonstration learning method (X) on learning motivation (Y1) and working skills (Y2) of the students at the hospitality and tourism services major. This research is using the quantitative approach with the experiment research. The research design on this research is using the one group pre test – post test design. The subjects of this research are all of the 12th grade students at Permahisa vocational school. This research is using observation and questionnaire data collecting technique. The questionnaire is divided into two parts, pretest and posttest. The instruments in this research is the validity and reliability test. The prerequisite test in this research is using the paired sample t-test. This fact could be proven from the paired sample t-test result. It showed that based on the pair 1 output, the value of t was at 50.454>2.086 (t-table) and sig.(2-tailed) was at 0.000<0.05 for the students’ learning motivation and the value of t was at 22.704>2.086 (t-table) and sig.(2-tailed) was at 0.000<0.05 for the students’ working skills. In conclusion, it could be said that there was a significant influence of the demonstration learning method on students’ learning motivation and working skills.